THE RELATIONSHIP BETWEEN MENARCHE KNOWLEDGE AND ANXIETY LEVELS IN ELEMENTARY SCHOOL STUDENTS AGED 11-12 YEARS AT SDN LIMUSNUNGGAL 01 BOGOR REGENCY IN 2022 - Fitria, Nabilah; Dinda Nur Fajri Hidayati Bunga; Hilda Meiryandah Agil (Soscience: Jurnal Ilmu Sosial Science, 2025)
Menarche which is often known as the beginning of maturity in young women is usually characterized by the beginning of the first menstruation is often considered a threat in the life of young women. One of the factors of a person who has a bad perception or attitude is the level of knowledge that a person has. Knowledge can affect the level of readiness in a person to face anything that the existence of ignorance will cause pressure on a person so that it causes anxiety. This study aims to determine the relationship between menarche knowledge and the level of anxiety of elementary school students aged 11-12 years at SDN Limusnunggal 01 Bogor Regency in 2022. The method used in this study is quantitative, which is analytical with a cross-sectional design. The sampling technique in this study was total sampling so that the sample in this study was the entire population of students of SDN Limusnunggal 01 totaling 135 and samples totaling 77 who had menarche. Data collection uses questionnaires/questionnaires for grade 5 students and google from for grade 6 students. Bivariate data analysis using chi square test. Statistical test using chi square test with the results of respondents who had less knowledge of menarche as many as 51 respondents (66.2%) and had a high level of anxiety as many as 44 respondents (57.1%) obtained p-value (0.000) < (0.05). There is a relationship between menarche knowledge and the anxiety level of elementary school students aged 11-12 years at SDN Limusnunggal 01 Bogor Regency in 2022.